2022
DOI: 10.1177/10963480221076474
|View full text |Cite
|
Sign up to set email alerts
|

Resident Empowerment and Support for Gaming Tourism: Comparisons of Resident Attitudes Pre- and Amid-Covid-19 Pandemic

Abstract: Grounded in Weber’s theory of formal and substantive rationality, this study aims to examine the influences of economic and noneconomic factors, namely resident empowerment and trust, on resident support for gaming tourism, a controversial type of tourism development. In particular, with data collected before and during the COVID-19 pandemic, the study also examines how resident perceptions of economic and noneconomic benefits of tourism have changed as a result of the pandemic. Findings show that perceived ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 69 publications
1
14
0
Order By: Relevance
“…A notable 2020 example is the Covid-19 pandemic. Health and government entities implemented measures against the virus, including confinement, distancing and closures (Li et al , 2023). Globally, the hospitality industry faced daily losses of around US$534m (Kostromitina et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A notable 2020 example is the Covid-19 pandemic. Health and government entities implemented measures against the virus, including confinement, distancing and closures (Li et al , 2023). Globally, the hospitality industry faced daily losses of around US$534m (Kostromitina et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Their studies revealed a direct relationship between resident empowerment and support for tourism. However, focusing on the context of gaming tourism during the COVID-19 period, X. Li et al (2022) found the effects of empowerment are mixed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, focusing on the context of gaming tourism during the COVID-19 period, X. Li et al (2022) found the effects of empowerment are mixed. Y.…”
Section: Resident Empowerment and Support For Tourismmentioning
confidence: 99%
“…Governments and municipalities cannot require communities to have positive perceptions of tourism development. However, trust in tourism policy is a condition under which local residents respond positively to the impact of tourism (Li et al, 2022). Particularly, in islands that are building social resilience through tourism, it is difficult for tourism policy makers to develop sustainable island tourism without the support from local residents (Aguiló & Rosselló, 2005;Wu et al, 2020).…”
Section: Trust For Tourism Policy and Related Institutionmentioning
confidence: 99%
“…Studies have indicated that, in times of economic uncertainty, residents' perceptions are affected by various economic and psychological concerns (Garau-Vadell et al, 2018;. The recent COVID-19 pandemic has paralysed economic and social activities in countries and regions, and its impact cannot be fully predicted (Gössling et al, 2021;Li et al, 2022).…”
Section: Trust For Tourism Policy and Related Institutionmentioning
confidence: 99%